Effectiveness of maternal pertussis vaccination in Singapore: A test-negative case-control study. Issue 46 (2nd November 2022) - Chong, Chia-Yin; Tan, Natalie Woon-Hui; Yung, Chee-Fu; Li, Jiahui; Kam, Kai-Qian; Nadua, Karen; Maiwald, Matthias; Sultana, Rehena; Thoon, Koh Cheng
Abstract: Pertussis vaccination (Tdap -Tetanus-diphtheria-acellular pertussis) for pregnant women has been recommended since November 2017 in Singapore. In this prospective test-negative case-control study from 2018 to 2019, we aimed to evaluate vaccine effectiveness (VE) against pertussis infection and pertussis-related intensive care unit (ICU) admission according to Tdap (Tetanus-diphtheria-acellular pertussis) during pregnancy and/or infant pertussis vaccination. A total of 58 children (26 cases, 32 controls) were recruited with 4 ICU admissions. The median age was 3 months (interquartile range [IQR] 1.50–4.56 months). Overall, 25.9 % of mothers had received antenatal Tdap vaccination and 43.1 % of infants received pertussis vaccination, majority only 1 dose. Tdap in pregnancy alone without infant vaccine or with 0–1 infant dose had a VE of 97.62 % (95 % confidence interval [CI] 53.25–99.88 %), 98.17 % (95 %CI 66.61–99.9 %) respectively, against pertussis infection and 71.9 % (95 %CI 0.0–98.64), 75.86 % (95 % CI 0.0–98.78) respectively, against ICU admissions. Conclusion: Maternal Tdap vaccination was highly protective against infant pertussis and should be routinely recommended for all pregnant women.